2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.143
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination and Impact of Multi-criteria Decision Support Methods for IT Project Evaluation

Abstract: The aim of this paper is to demonstrate whether knowing or applying selected multi-criteria decision support (MCDS) methods make decisions more effective or efficient in the context of IT project proposals. Results from a nationwide empirical survey conducted in Austria (N = 114) show a method diffusion -infusion gap. In other words, many organizations are aware of MCDS methods but do not apply these methods in IT evaluation practice. We show that knowing or using MCDS methods increases decision effectiveness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…At the main stage of this study, we concluded that the method succeeded in parsing the draw voting process by developing it by adding a winning gap (distance) between alternatives during the pairwise contest and then multiplying the existing gap by the weight or population of DM. the results of the model trial case study, the voting results of all DMs on ten (10) ICT projects in the Palembang city government, it was found that and also the results of the sensitivity test against the three criteria affected project evaluation. In the future, we will try a ranking system to get results that can determine transparent winners in a project in government.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the main stage of this study, we concluded that the method succeeded in parsing the draw voting process by developing it by adding a winning gap (distance) between alternatives during the pairwise contest and then multiplying the existing gap by the weight or population of DM. the results of the model trial case study, the voting results of all DMs on ten (10) ICT projects in the Palembang city government, it was found that and also the results of the sensitivity test against the three criteria affected project evaluation. In the future, we will try a ranking system to get results that can determine transparent winners in a project in government.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the effectiveness and efficiency of evaluation are increasingly important for a project [15]. In this regard, several researchers have implemented MCDM methods, both in the DSS or SPKK [16][8][9] [10]. Many organizations realize the importance of the MCDM method because the use of the MCDM method increases effectiveness in decisionmaking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been many previous studies using this method, such as [4]; [5]); [6]); [7]; [8]); [9]. One popular method used for it is the Analytic Hierarchy Process (AHP).…”
Section: Introductionmentioning
confidence: 99%